Lipidomic profiling provides insights on Arabica coffee flavor diversity in different postharvest processing methods - Yanbing Wang; Xiaoyuan Wang; Ping Du; Xiaogang Liu; Sufang He; Lirong Li; Xiaoqiong Liu; Zhenjia Chen (Current Research in Food Science)
The processing methods of coffee cherries after harvesting can significantly affect the lipid composition of green coffee beans, thereby influencing their in-cup properties. This study utilized ultra-high performance liquid chromatography-electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) technology to investigate the impact of natural, washed, and honey processing methods on the lipid composition of green coffee beans, accompanied by sensory evaluations. A total of 510 lipids, covering 27 subclasses, were detected. Of these, 150 lipids showed significant differences before and after processing, and 37 lipids were identified as potential biomarkers for distinguishing the three processing methods. Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathway analysis revealed that glycerophospholipid metabolism was the key pathway for the formation of differential lipids among the various processing methods. Significant correlations were observed between lipid composition and the flavor diversity associated with different processing methods. The findings provide a crucial basis for understanding the lipid transformation of coffee during different processing methods and its impact on flavor quality characteristics.